DEVELOPING STUDENTS’ VOCABULARY WORKSHEET USING SCIENTIFIC APPROACH ON WRITING DESCRIPTIVE TEXT FOR THE SEVENTH GRADE STUDENTS AT SMP NEGERI 2 BABALAN - Amalia Chandra Dewi; Rahmad Husein; Safrida Lubis (Universitas Negeri Medan, 2021)
DEVELOPING STUDENTS’ VOCABULARY WORKSHEET USINGSCIENTIFIC APPROACH ON WRITING DESCRIPTIVE TEXT FORTHE SEVENTH GRADE STUDENTS AT SMP NEGERI 2 BABALAN*Amalia Chandra Dewi**Dr. Rahmad Husein, M.Ed.**Safrida Lubis, S.Pd., M.Hum.ABSTRACTSDewi, Amalia Chandra. Registration Number: 2133121003. DevelopingStudents’ Vocabulary Worksheet using Scientific Approach on WritingDescriptive Text for the Seventh Grade Students at SMP Negeri 2 Babalan. AThesis. English Education Program, State University of Medan, 2020.The aimed of this study was to develop students’ vocabulary worksheet based onscientific approach on writing descriptive text for seventh grade students at SMPNegeri 2 Babalan. This study was conducted by using Research and Development(R&D) design through six stages; gathering information and data, analyzing data,designing materials, validating by experts, revising, and final product.The subjectof the study was grade VII of SMP Negeri 2 Babalan. The instruments of datacollection were gathered by administering interview and distributingquestionnaire. The study conducted interview to the English teacher anddistributing questionnaire to 27 respondents to get the students’ needs. Theinterview and questionnaire results proved that the students need vocabularyworksheet based on scientific approach in writing descriptive which can helpstudents to enrich the vocabulary. The product has been validated by an Englishlecturer and an English teacher with the average score is 4.6. The product wascategorized as “Very good” students’ vocabulary worksheet in writing descriptivetext. The final product of this study was a set of developed students’ vocabularyworksheet in writing descriptive text, it consisted five parts which were adaptedfrom Scientific Approach. Every part has 3-5 tasks that covered the learningneeds. It also has key words and the topics that are going to be done by thestudents in the first page of every part of the worksheet.Keywords : Vocabulary, Worksheet, Scientific Approach, Research andDevelopment (R&D), Writing Descriptive Text